STUDY OF THE WATER QUALITY OF ALQUEVA ARTIFICIAL LAKE IN THE SOUTH OF PORTUGAL USING MERIS DATA - Potes, Miguel (2012)
The successful launch of ENVISAT in March 2002 has given a great opportunity to understand the changes of water colour with high spatial resolution. In this study, the potential of MERIS sensor to describe variations of optically active substances of Alqueva artificial lake is investigated. Regular in situ measurements, from May 2004 to July 2005, are used in combination with MERIS acquisitions. The surface reflectance is derived from Level 1b MERIS data, using radiative transfer calculations to account for the atmospheric effects. The parameterizations obtained are used to map the concentrations of chlorophyll-a, cyanobacteria and suspended sediments. The results obtained are